INFLUENCE OF BEHAVIORAL FACTORS ON HEALTH INDICATORS OF SCHOOL STUDENTS AT THE REGIONAL LEVEL - Holovanova, I.A.; Lesko, O.M.; Obrevko, N.O.; Liakhova, N.O.; Bielikova, I.V. (World of Medicine and Biology, 2022)
The article analyzes the state of health of schoolchildren aged 10–15 in Kremenchuk and investigates the influence of behavioral risk factors. It was established that the movement activity of schoolchildren is insufficient, 19.2 % have an increased BMI. Detected violations of food behavior, manifested in the replacement of a “healthy snack” with sweets in 30.8 % or refusal of snacks in 12.2 %. 12.8 % of schoolchildren note insufficient duration of night sleep, which leads to overtiredness. It has been established that children 13–15 years are significantly less engaged in physical education; do not follow the rest regime, reducing the time of night sleep; they use fruits, vegetables or yogurts for snacks much less often, preferring snacks and sweets. It was found that 56.4 % of children get sick more than once a year, the influence of behavioral risk factors on the frequency of colds was proven: children who did not do physical education were 3 times more getting colds than those who did active lifestyle; “unhealthy” snacking on sweets and snacks increased the risk of frequent colds by 2 times.